TATA KELOLA PENDIDIKAN ISLAM: STRATEGI MANAJEMEN DAN TANTANGAN KONTEMPORER - Anshory, Shofyan; Citriadin, Yudin; Maujud, Fathul (Program Studi Manajemen Pendidikan Islam, 2024)
It is essential for Islamic education to shape the character and knowledge of Muslims all over the world. A good governance of Islamic education is essential to guaranteeing the quality and relevance of education. The study investigates Islamic education governance, management approaches used, and current problems faced by Islamic educational institutions. The study aims to improve understanding of management practices and governance in Islamic Education by collecting and analyzing relevant literature through qualitative methods and library study approaches. Research shows that the use of information technology, teacher professional development, and school-based management (MBS) are effective management strategies. Information technologies such as e-learning platforms and school information management systems (SMIS) improve access to education and increase administrative productivity. According to this study, improving the quality and relevance of Islamic education in the modern era requires change and innovation in management strategies. This study concludes that to improve the quality and relevance of Islamic education in the modern era, changes and innovations in management strategies are needed.